Would I Really Make a Difference? Moral Typecasting Theory and its Implications for Helping Ethical Leaders - Yam, Kai Chi (Journal of business ethics, 2019)
Ethical leadership research has primarily relied on social learning and social exchange theories. Although these theories have been generative, additional theoretical perspectives hold the potential to broaden scholars’ understanding of ethical leadership’s effects. In this paper, we examine moral typecasting theory and its unique implications for followers’ leader-directed citizenship behavior. Across two studies employing both survey-based and experimental methods, we offer support for three key predictions consistent with this theory. First, the effect of ethical leadership on leader-directed citizenship behavior is curvilinear, with followers helping highly ethical and highly unethical leaders the least. Second, this effect only emerges in morally intense contexts. Third, this effect is mediated by the follower’s belief in the potential for prosocial impact. Our findings suggest that a follower’s belief that his or her leader is ethical has meaningful, often counterintuitive effects that are not predicted by dominant theories of ethical leadership. These results highlight the potential importance of moral typecasting theory to better understand the dynamics of ethical leadership.